Comparing the Effectiveness of Dietary Vitamin C and Exercise Interventions on Fertility Parameters in Normal Obese Men - Rafiee, Bahare; Morowvat, Mohammad Hossein; Rahimi-Ghalati, Nasrin (Urology Journal, 2016)
Purpose: Comparing the effectiveness of dietary vitamin C and weight loss exercises interventions for weight loss on semen characteristics in normal obese man. Materials and Methods: A total number of 200 men were randomly allocated into two groups based on body mass index, exercise and vitamin C groups. Also, 50 men with normal spermogram were placed in a control group. In exercise group, a 6 months intensive exercise program was designed under a coach's supervision to reduce the body weight. In vitamin C group, 1,000 mg of vitamin C were given every other day as supplement. Results: Weight loss increased the volume of semen in participants with 25-30 (P = .02) and more than 30 body mass index (P = .001). The increased concentration of sperm per mL of semen in body mass index (BMI) 25-30 group (P = .01) and more than 30 (P = .003) BMI was significant. Improving sperm motility after two hours in participants with more than 30 (P = .01) BMI was significant. In vitamin C group, the improvement of sperm concentration in participants who had less than 25 (P = .01), between 25 and 30 (P = .01), more than 30 (P = .02) BMI was significant. Sperm motility improved in all three groups (P = .001, P = .02 and P = .003, respectively). Conclusion: Weight loss can significantly increase semen volume, its concentration, its mobility and percentage of normal morphology. Consuming vitamin C significantly improves sperm concentration and mobility, but the semen volume and the percentage of normal morphology will not change significantly.